Comparative histological analysis of drug‐induced maculopapular exanthema and DRESS. (16th July 2016) - Skowron, F.; Bensaid, B.; Balme, B.; Depaepe, L.; Kanitakis, J.; Nosbaum, A.; Maucort‐Boulch, D.; Bérard, F.; D'Incan, M.; Kardaun, S.H.; Nicolas, J.‐F.
Abstract: Background: Cutaneous adverse drug reactions frequently present as a benign maculopapular exanthema (MPE) with a rapid healing. Sometimes systemic signs are present, which could represent a more severe or systemic MPE (sMPE) or even be the initial phase of a drug reaction with eosinophilia and systemic symptoms (DRESS). Histopathology associated with MPE, sMPE and DRESS has not been well characterized. Objectives: To study the cutaneous histopathological changes associated with MPE, sMPE and DRESS. Methods: A retrospective clinicopathological analysis of 13 cases of MPE, 13 of sMPE and 45 of DRESS, collected in one centre from 2005 to 2013. Results: The number of histopathological changes per section increased gradually from MPE to sMPE and DRESS. Prevalence of spongiosis, dermal lymphocytes, eosinophils and neutrophils did not differ between MPE, sMPE and DRESS. Keratinocyte damage, rare in MPE, was regularly found in sMPE and frequent in DRESS. The density of the inflammatory infiltrate increased progressively from MPE to sMPE and DRESS. Atypical lymphocytes were absent in MPE, present in sMPE and more frequent in DRESS. Deep dermal involvement and leukocytoclastic vasculitis were only observed in DRESS. Limitations: This was a retrospective study. Conclusions: Numerous histopathological changes per section in drug‐induced exanthema should alert for a more severe form of cutaneous adverse drug reactions, i.e. DRESS.